Drivers of Potential Recharge from Irrigated Agroecosystems in the Wisconsin Central Sands - Nocco, M.A. (2020)
We found that interannual climate variability, subtle differences in soil texture, and cropping system type drove potential recharge to varying degrees during the summer and fall seasons. Relatively finer soil texture was positively correlated to point estimates of potential recharge. This correlation was the strongest following large precipitation events. June to November cumulative potential recharge for 2013 to 2016 averaged 71 ± 235 mm across all lysimeters. Our findings suggest that aquifer depletion will be an episodic process that leaves surface waters most vulnerable to pumping and recharge impacts during and following drier years in the WCS. Differences among cropping systems were most pronounced under average precipitation conditions, which facilitated potential groundwater losses under field corn and pea–pearl millet rotations and potential groundwater gains under potato rotations. We conclude that regional water management strategies could be effective in buffering against the interannual climate variability of recharge, while localized management strategies could increase irrigation efficiency by targeting crop and soil textural drivers.